A discourse analysis of electronic cigarette videos on youtube - Kelebek, Özge; Karaman, Hakan; Yaman, Ömer Miraç (Journal of Dependence, 2022)
Objective: This study was carried out to determine the prominent elements in electronic cigarette videos that meet the audience on YouTube.Method: In this study, electronic cigarette videos published in Turkish on Youtube were examined by discourse analysis technique. In this context, the discourses in the video contents were taken as data. For this purpose, 60 videos that were reached in the criteria suitable for the study were included. Results: The results are presented thematically under the headings of “Affirmations about the Device”, “Warnings about the Device” and “Comparison with Smoking”.Conclusion: According to these results, it is seen that the electronic cigarette videos in circulation are mostly designed in the form of advertisement and promotional content, and the product is promoted as a more effective, cheap and harmless product compared to traditional cigarettes. Also, the image that it can be used to reduce the harms of traditional cigarettes or to terminate its use has come to the fore. Although there are technical warnings about the use of the device in some videos, it has been determined that a negative perception of electronic cigarettes is not conveyed in the videos. In addition, it has been determined that it is a tobacco use method equivalent to traditional cigarettes as a cheaper and harmless product and its use is encouraged in this respect.
Keywords: Electronic cigarette; YouTube; discourse analysis